Peningkatan Kreativitas Anak dengan Membuat Kerajinan Tangan dari Limbah dan Kardus Bagi Anak di Desa Pandansari Selatan, Kecamatan Sukoharjo, Kabupaten Pringsewu - Wahyudi, Dedi; Nuryah, Nuryah; Rindiana, Bunga; Putri, Dania Mutiara (Wisanggeni: Jurnal Pengabdian Masyarakat, 2022)
Children in the village of South Pandansari tend to prefer playing with their cellphones, watching TV and playing with their friends rather than taking advantage of the time they have. Service activities in the form of making crafts using used goods that can be utilized. The community service team carried out this activity at the Reading Corner, to be precise, in Pandan Sari Selatan Village, Sukoharjo District, Pringsewu Regency. So that children in South Pandansari Village can work from an early age. The community service and empowerment method used is ABCD (Asset Based Community Development). The results of the community service activities that have been carried out are teaching the children of South Pandansari village to work in utilizing used goods, to start practicing creative thinking from an early age for their future and to take advantage of their free time so they are not consumed by negative things. The programs that have been implemented can be used as a reference and input to add experience or skills and encourage the creation of a more active, dynamic, healthy and prosperous society and can serve as an example for other sub-districts or villages.